2001
DOI: 10.1002/mrd.1114
|View full text |Cite
|
Sign up to set email alerts
|

Solubilized zona pellucida proteins and progesterone induce calcium influx and the acrosome reaction in capacitated dog spermatozoa

Abstract: Spermatozoa from the sperm-rich fractions of the semen of 6 beagle dogs were capacitated and the effect of both zona pellucida (ZP) proteins and progesterone on calcium flux and the acrosome reaction measured. Sperm calcium flux was determined using the dual wavelength calcium probe indo-1/AM (6 microM) in a flow cytometric assay (one ejaculate from each dog examined; n = 6). No calcium flux was observed in the negative control treatments (RPMI medium or DMSO). Both heat-solubilized bitch ZP proteins and proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The latter may include a rise in progesterone concentrations and factors deriving from the maturing oocytes [10,40,41]. In our study despite the low sperm numbers detected in oviduct flushing, viable sperm were found both 2 days and 4 days after ovulation with a maximum proportion of 60% motile spermatozoa (group 2) similar to the in vitro findings of England and Pacey (1998) [42] and Pacey et al (2000) [43].…”
Section: Discussionsupporting
confidence: 88%
“…The latter may include a rise in progesterone concentrations and factors deriving from the maturing oocytes [10,40,41]. In our study despite the low sperm numbers detected in oviduct flushing, viable sperm were found both 2 days and 4 days after ovulation with a maximum proportion of 60% motile spermatozoa (group 2) similar to the in vitro findings of England and Pacey (1998) [42] and Pacey et al (2000) [43].…”
Section: Discussionsupporting
confidence: 88%
“…It can be argued that P facilitated IVF by promoting both hyperactivation and the acrosome reaction. Many studies report that this hormone, secreted by cumulus cells and contained in FF, induces AR in human (Meizel and Turner 1991;Baldi et al 1998), mouse (Roldan et al 1994), boar (Melendrez et al 1994), stallion (Meyers et al 1995;Cheng et al 1998), golden hamster (Llanos and Anabalón 1996), dog (Brewis et al 2001) and caprine (Somanath et al 2000) spermatozoa. Progesterone also affects human sperm capacitation (Foresta et al 1992;Uhler et al 1992;Luconi et al 1995) and increases the ability of mouse spermatozoa to respond to the zona pellucida (Roldan et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…1995), caprine (Somanath et al. 2000), canine (Brewis et al. 2001) and golden hamster (Meizel et al.…”
Section: Introductionmentioning
confidence: 99%